Customary Settlement of Certain Criminal Cases in the Indigenous Community of Kenegerian Benai, Kuantan Singingi - Effendi, Erdianto; Putra, Setia (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2022)
This study analyzed the resolution of specific criminal cases within the indigenous peoples of Kuantan Singingi, Riau. The shift in customary laws towards a modern legal system has caused various problems, including accumulating case files and overcapacity in prisons. This occurred because the community has also lost its grip on solving problems with the existing customary laws. Therefore, this study involved interviews with chairpersons, secondary leaders, customs on conflict resolution among indigenous peoples, and the use of primary data. The results highlighted that the customary settlement of criminal cases can sufficiently resolve conflicts in the community. Furthermore, it overcame the accumulation of case files in the courts and overcapacity in penitentiary institutions.